2015
DOI: 10.5027/andgeov42n1-a06
|View full text |Cite
|
Sign up to set email alerts
|

Márgenes costeros híbridos de la Cuenca Neuquina (Formación Allen, Cretácico Superior, Argentina).

Abstract: ABSTRACT. The Allen Formation records the first Ingression Atlantic to the Neuquén Basin during the Late Cretaceous. The definition of lithofacies and facies associations interpretation for stratigraphic sections in Paso Córdoba and Salitral Moreno area, Río Negro, Argentina allowed to establish the depositional system that characterized this transgression in the northeastern edge of the Basin. In this paper we present sedimentological analysis of conglomeratic, sandstone, heterolithic and pelitic facies, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…unconformity (e.g., Hugo and Leanza, 2001;Leanza et al, 2004;Leanza, 2009;Garrido, 2010). However, there is no uniformity of criteria regarding this limit in the Paso C ordoba area, so both a transitional (see Paz et al, 2014;Armas and S anchez, 2015) and an erosive discordance (Hugo and Leanza, 2001) have been suggested.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…unconformity (e.g., Hugo and Leanza, 2001;Leanza et al, 2004;Leanza, 2009;Garrido, 2010). However, there is no uniformity of criteria regarding this limit in the Paso C ordoba area, so both a transitional (see Paz et al, 2014;Armas and S anchez, 2015) and an erosive discordance (Hugo and Leanza, 2001) have been suggested.…”
Section: Geological Settingmentioning
confidence: 99%
“…The Huantraiquican unconformity is well exposed in the area of Cinco Saltos and Lago Pellegrini, both in the Río Negro province (Leanza, 2009), but in Paso C ordoba its existence is discussed. Hugo and Leanza (2001) suggested that, in fact, there is an erosive discordance between the red/purple mudstone of the Anacleto Formation and the yellowish sandstones of Allen Formation, but Paz et al (2014) and Armas and S anchez (2015) have recently studied some stratigraphical sections in that area and proposed a transitional passage between both formations, which would owe to the gradual evolution of the depository system. According to the stratigraphical, facial and palaeoenvironmental analyses presented in this contribution, we observed no clear changes or unconformities in the Cañad on del Desvío, which would allow a reinforce the proposal of transitional passage between both formations.…”
Section: Contribution To the Vertebrate Diversity Of The Anacleto Andmentioning
confidence: 99%